Escreva a Equação
![5 - \frac{(x - 3)}{4} = 2x - (x - {2}^{)2} 5 - \frac{(x - 3)}{4} = 2x - (x - {2}^{)2}](https://tex.z-dn.net/?f=5+-++%5Cfrac%7B%28x+-+3%29%7D%7B4%7D++%3D+2x+-+%28x+-++%7B2%7D%5E%7B%292%7D+)
na forma
![a {x}^{2} + bx + c = 0 a \: diferente \: de \: 0 a {x}^{2} + bx + c = 0 a \: diferente \: de \: 0](https://tex.z-dn.net/?f=a+%7Bx%7D%5E%7B2%7D++%2B+bx+%2B+c+%3D+0+a++%5C%3A+diferente+%5C%3A+de+%5C%3A+0)
Soluções para a tarefa
Respondido por
1
Perguntas interessantes
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Português,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
Geografia,
1 ano atrás